2020
DOI: 10.1038/s41419-020-03191-5
|View full text |Cite
|
Sign up to set email alerts
|

A small natural molecule CADPE kills residual colorectal cancer cells by inhibiting key transcription factors and translation initiation factors

Abstract: Residual disease is the major cause for colorectal cancer (CRC) relapse. Herein, we explore whether and how a natural molecule CADPE killed heterogenic populations in a panel of CRC cell lines with KRAS/BRAF mutations that are natively resistant to EGFR- or VEGFR-targeted therapy, without sparing persistent cells, a reservoir of the disease relapse. Results showed that CADPE killed the tumor bulk and residual cells in the panel of CRC cell lines, rapidly inactivated c-Myc, STAT3, and NF-κB, and then decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…S3 A). Compared with the control group (C group), overexpression of WWTR1-AS1 and Notch3 was observed to enhance the stemness of CSCC cells, reflected by the increase in the percentage of CD133 + cells [ 18 , 19 ]. The overexpression of miR-136 led to a reduction in CSCC cell stemness and counteracted the effects of WWTR1-AS1 and Notch3 overexpression on CSCC cell stemness.…”
Section: Resultsmentioning
confidence: 99%
“…S3 A). Compared with the control group (C group), overexpression of WWTR1-AS1 and Notch3 was observed to enhance the stemness of CSCC cells, reflected by the increase in the percentage of CD133 + cells [ 18 , 19 ]. The overexpression of miR-136 led to a reduction in CSCC cell stemness and counteracted the effects of WWTR1-AS1 and Notch3 overexpression on CSCC cell stemness.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in Kras, BRAF, BIM polymorphism de ciency and EML4-ALK fusion gene mutations are the primary resistance mechanisms against EGFR inhibitors (33). In a PDX model of mouse lung adenocarcinoma, Emilio's team found that EGFR signaling is involved in K-Ras-driven lung tumorigenesis in both humans and mice.…”
Section: Discussionmentioning
confidence: 99%